A spoonful of salt helps the medicine go down…. Issue 7 (20th July 2022) - Thompson, Angus
Abstract : … but not in a delightful way. Some patients prefer to take their medicines as soluble tablets, but these products sometimes contain clinically significant amounts of sodium, which if taken regularly at high doses can add up to the equivalent of an alarming amount of salt, cautions Angus Thompson.